Ethics in Virtual Reality (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Virtual Reality (VR) has revolutionized the way humans interact with digital environments, offering unprecedented levels of immersion and engagement. While the technological advancements are impressive, the ethical implications of VR remain underexplored and complex. This article investigates the ethical challenges arising from the use of VR across various domains including entertainment, journalism, education, healthcare, and social interaction. Topics such as user consent, psychological impact, data privacy, identity manipulation, and the moral obligations of content creators are critically analyzed. By examining these issues through a multidisciplinary lens, the paper advocates for the development of comprehensive ethical frameworks to guide responsible VR implementation. The study emphasizes the urgent need for proactive ethical regulation and professional standards to ensure that VR enhances rather than harms human experience.